TRANSFORMATION OF ISLAMIC BOARDING SCHOOLS; IMPROVING SERVICE QUALITY WITH THE PEDATREN MANAGEMENT INFORMATION SYSTEM - Muchyiddin, Achmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research is intended to analyze and understand the use of the Pedatren application system as a response to the modernization occurring at the Nurul Jadid Islamic boarding school, Paiton, Probolinggo, with the aim of improving service quality. The research method used is a qualitative approach with a case study type. Data collection was carried out through observation, interviews and documentation. Data analysis begins with presenting the data, carrying out data reduction, and ends with concluding the findings. The research results show that the use of the Pedatren application system can respond to the challenges of Islamic boarding school modernization and the complexity of community demands amidst competition between educational institutions. This is achieved through providing services related to student identity, number of students, development of the student learning process, student licensing system, and payments made digitally via virtual accounts.